Postconflict reconciliation: intergroup forgiveness and implicit biases in Northern Ireland - Tam, Tania (Journal of social issues, 2008)
Even after a conflict has formally ended, there is still a need for postconflict reconciliation and the building of mutual forgiveness and trust between communities. This article addresses psychological processes crucial to moving beyond a history of violent sectarian conflict in Northern Ireland. We investigated the predictors of intergroup forgiveness, in terms of intergroup emotions, infrahumanization, empathy, and intergroup contact. Intergroup trust and measures of implicit intergroup bias were also explored in this area of real intergroup conflict. The results are discussed in terms of their implications for postconflict reconciliation in Northern Ireland and other conflict areas.